Effect of a Nutritional Education Intervention on the Reduction of Added Sugar Consumption in Schoolchildren in Southeastern Mexico: Community Study - Carmen Morales-Ruán; Teresa Shamah-Levy; Danae Gabriela Valenzuela-Bravo; Rebeca Uribe-Carvajal; Corin Hernández-Palafox; María Concepción Medina-Zacarías; Ignacio Méndez Gómez-Humarán (Foods)
Consumption of added sugars negatively affects schoolchildren’s health, making it essential to promote strategies designed to reduce their intake through educational interventions. This study aimed to evaluate the effect of a nutritional education intervention, INCAI, on the consumption of added sugars among schoolchildren in southeastern Mexico. A 9-month educational intervention was designed to promote healthy eating, physical activity, and the development of socio-emotional skills among primary school children. Information on the usual intake of foods and beverages was collected from 400 schoolchildren at the beginning and end of the intervention using a semiquantitative food frequency questionnaire. For the analysis, a generalized estimating equation (GEE) model was constructed using the Poisson distribution family to estimate the effect of the intervention. The relative incidence in the final stage showed a slight increase of 4% (p = 0.093) in the percentage of added sugars compared with the baseline levels in the control group. By contrast, the intervention effect, represented by the interaction between treatment and time, showed a 10% reduction in the final stage in the intervention group (p < 0.001). Based on these findings, the INCAI educational intervention effectively reduced added sugar consumption by 10% in the intervention group, while no significant reduction was observed in the control group. These results suggest that nutritional education programs can be a useful strategy for lowering added sugar intake among schoolchildren, highlighting the importance of incorporating such interventions into public health policies targeting child populations.